Managing urban growth at the regional level: A review of the International Literature; Regionales Wachstumsmanagement: Eine Analyse der internationalen Literatur - Stefan Siedentop; Stephan Schmidt; Alistair Dunlop (Raumforschung und Raumordnung / Spatial Research and Planning, 2022)
Today, most countries in the global north have developed and implemented urban growth management (UGM) programs and policies aimed at mitigating the impacts and negative externalities of urban sprawl and achieving a more compact urban form. However, there is substantial disagreement about their effectiveness and effects of these programs. In this paper, we systematically review the extensive literature on growth management to better understand a) the current state of the practice of UGM, and b) the determinants of successful UGM implementation. Compared to previously available literature syntheses, which focus heavily on North American research, we also take into account studies based in Europe and some Asian and Oceanic countries. From this literature, we identify several key factors to successful growth management implementation: a multi-level governance approach, intersectoral policy coordination, a regionally adapted mix of policy instruments, balancing development needs with preservation goals, and the ability to develop positive narratives around growth management. – – In den meisten Länder des globalen Nordens existieren heute Programme und Strategien zur Steuerung des urbanen Wachstums. Diese zielen darauf ab, die negativen externen Effekte der Zersiedelung zu mindern und eine kompakte Stadtentwicklung zu gewährleisten. Über die Wirksamkeit und die Auswirkungen dieser Programme herrscht jedoch große Uneinigkeit. In diesem Beitrag wird die umfangreiche Literatur zum Thema Wachstumsmanagement systematisch ausgewertet, um a) den aktuellen Stand der Fachpraxis und b) die Determinanten einer erfolgreichen Umsetzung besser zu verstehen. Im Vergleich zu früheren Literatursynthesen, die sich stark auf die nordamerikanische Forschung konzentrieren, berücksichtigen wir auch Studien aus Europa und einigen asiatischen und ozeanischen Ländern. Basierend auf der Literatur identifizieren wir mehrere Schlüsselfaktoren für eine erfolgreiche Umsetzung des Wachstumsmanagements: ein Multi-Level-Governance-Ansatz, sektorübergreifende Politikkoordination, ein regional angepasster Mix von Instrumenten, ein Ausgleich zwischen den Anliegen der Baulandversorgung und dem Flächenschutz sowie die Fähigkeit, positive Narrative des Wachstumsmanagement zu entwickeln.
Keywords: 710; Urban growth management; regional planning; land use planning; governance; literature review; Urbanes Wachstumsmanagement; Regionalplanung; Flächennutzungsplanung; Governance; Literaturanalyse